2021
DOI: 10.3390/molecules26040967
|View full text |Cite
|
Sign up to set email alerts
|

Boulton-Katritzky Rearrangement of 5-Substituted Phenyl-3-[2-(morpholin-1-yl)ethyl]-1,2,4-oxadiazoles as a Synthetic Path to Spiropyrazoline Benzoates and Chloride with Antitubercular Properties

Abstract: The analysis of stability of biologically active compounds requires an accurate determination of their structure. We have found that 5-aryl-3-(2-aminoethyl)-1,2,4-oxadiazoles are generally unstable in the presence of acids and bases and are rearranged into the salts of spiropyrazolinium compounds. Hence, there is a significant probability that it is the rearranged products that should be attributed to biological activity and not the primarily screened 5-aryl-3-(2-aminoethyl)-1,2,4-oxadiazoles. A series of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Their structures have been determined by the complex use of spectroscopic methods, as well as X-ray structural analysis (Kayukova, 2003;Beketov et al, 2004;Kayukova et al, 2010a). The dehydration of the products of the O-acylation of -aminopropioamidoximes allows for 3,5-disubstituted 1,2,4-oxadiazoles to be obtained, which under conditions of acid hydrolysis and in the presence of moisture are capable of undergoing a Boulton-Katritsky rearrangement to 2-amino-1,5-diazaspiro [4,5]dec-1-en-5-ium salts (Kayukova et al, 2010b(Kayukova et al, , 2018(Kayukova et al, , 2021a.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Their structures have been determined by the complex use of spectroscopic methods, as well as X-ray structural analysis (Kayukova, 2003;Beketov et al, 2004;Kayukova et al, 2010a). The dehydration of the products of the O-acylation of -aminopropioamidoximes allows for 3,5-disubstituted 1,2,4-oxadiazoles to be obtained, which under conditions of acid hydrolysis and in the presence of moisture are capable of undergoing a Boulton-Katritsky rearrangement to 2-amino-1,5-diazaspiro [4,5]dec-1-en-5-ium salts (Kayukova et al, 2010b(Kayukova et al, , 2018(Kayukova et al, , 2021a.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Essentially, 1,2- and 2,3-spiro-1-pyrazolines exist as spiro-2-pyrazolines (∆2 isomers) [ 3 ], although, in solutions, they exhibit an equilibrium of the imine and enamine forms [ 4 ]. As we know, the spiropyrazolinium salts with a 1,5-diazaspiro-1-en-5-ium fragment that we obtained via the hydrolysis of 3-(β-heteroamino)ethyl-5-aryl-1,2,4-oxadiazoles and the arylsulfochlorination of β-aminopropioamidoximes exist, under standard conditions, as the ∆2 isomer [ 5 , 6 , 7 , 8 ]. The thermodynamic advantage of possible tautomers of the key pyrazoline moiety was estimated; it turns out that, in the case of pyrazolines, the ∆2 isomer is much more stable than the others [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we obtained new spiropyrazolium compounds via the hydrolysis of 3-(β-heteroamino)ethyl-5-aryl-1,2,4-oxadiazoles [ 5 , 6 ], by the arylsulfochlorination (Aryl: para -XC 6 H 4 SO 2 Cl; X=CH 3 O, CH 3 , H, Br, Cl, NO 2 ) of β-(morpholin-1-yl)aminopropioamidoxime [ 7 ] and by the tosylation of β-aminopropioamidoximes (β-amino group: piperidin-1-yl, morpholine-1-yl, thiomorpholin-1-yl, 4-phenylpiperazin-1-yl, benzimidazol-1-yl) at r.t. [ 8 ]. In the present study, we are interested in the regioselectivity of β-aminopropioamidoximes ortho -, para -nitrobenzenesulphochlorination at reaction conditions (chloroform (CHCl 3 ), diisopropylamine (DIPEA), room temperature and 70 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Aminopyrazolinium-containing salts also possess inflammation, analgesic and antibacterial properties (Dusza et al, 1982a,b). Some of the authors found antitubercular activity for spiropyrazolinium benzoates and chlorides (Kayukova et al, 2021b), as well as antitubercular and antidiabetic activity in a series of -aminopropioamidoxime derivatives (Kayukova et al, 2018a(Kayukova et al, ,b, 2022a. Taking into account that the bioactivity of this family can be tuned by the nature of the parent -aminopropioamidoxime or the counter-ion in the reaction products, the screening of other derivatives of -aminopropioamidoximes for their antitubercular and antidiabetic activity is of practical interest.…”
Section: Introductionmentioning
confidence: 99%